Manajemen Sanggar Tari Galatiak Pitameh Kota Padang - Arimbi Wulandari; Wimbrayardi Wimbrayardi (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This study aims to describe the Management of Performing Arts at the Galatiak Pitameh Studio. This research is a qualitative research with a descriptive type. This research was conducted at the Galatiak Pitameh Studio in Padang City. The object of the research is the Galatiak Pitameh studio in Padang City. Data Collection Techniques with interviews, documentation and direct observation in the field. While the data analysis used in this study is an interpretation technique. The results of the research show that the management of the Galatiak Pitameh Studio has planning by making programs that will be carried out and will be implemented, with the preparation of equipment and training. Organizing has been carried out by making a line-shaped management structure. The organization also establishes the duties and authority of the management. The mobilization is carried out by providing motivation, guidance and moving towards the set goals. Internal supervision is carried out directly or indirectly, then external supervision with activity evaluation. The Galatiak Pitameh studio also has House productions consisting of dance, music, and babako. The marketing management of Sanggar Galatiak Pitameh also keeps up with the times. The Galatiak Pitameh Studio has been registered with Tourism and collaborates with Tourism. Of the two management chosen by the Galatiak Pitameh Studio, the management used shows democracy.